IMPLEMENTATION OF COMMUNICATION PRINCIPLES IN INTERACTIONS BETWEEN STUDENTS AND TEACHERS AT AS'ADIYAH SANTAN TENGAH SCHOOL, EAST KALIMANTAN: A LIVING QURAN PERSPECTIVE - Suherman; Abdul Majid; Andi Darna (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This research aims to identify the character of students at Junior High School of As’adiyah, especially in the use of everyday language. The background to this research is based on the emergence of the phenomenon that a number of students are starting to get used to using rude and impolite language, which is thought to be the impact of gaming habits. To form good student character in communicating with teachers, efforts are needed to instill qur’anic values in a sustainable manner. The goal of this effort is for students to have a strong moral, so that they don’t just act politely in the school environment, but also able to apply the valuesthese in social life. This research uses Islamic Communication Theory with a living Qur’an approach, the values of the Qur’an are not only taught in the theory, but are familiarized in daily practice day. Through this approach, it is hoped that students will get used to communicating in polite and athical languageboth to teachers and to other people.